A survey study on integration of warehouses and distribution centres - Pek, Tingwei. (2011)
In order to synergize business to survive in this competitive world, organizations can adopt integration as a business strategy. This study examines such practices among the warehouses and distribution centres, with a focus on the logistics industry in Singapore. This research project was carried out by collecting survey data and conducting interviews with industry professionals in the data consolidation and analysis phase. The findings indicated that most logistics companies in Singapore did not perform integration. While those that adopted integration as part of their business strategy preferred horizon integration to vertical integration according to our survey results. Our interview results revealed that companies are engaged in a mixture of both types of integration in equal proportions.